Hepatocyte expression and prognostic importance of senescence marker p21 in liver histopathology samples from dogs with chronic hepatitis. (22nd August 2018) - Kortum, Andre J.; Cloup, Emilie A.; Williams, Tim L.; Constantino‐Casas, Fernendo; Watson, Penny J.
Abstract : Background: Chronic hepatitis (CH) occurs commonly in dogs but is associated with a variable and largely unpredictable prognosis. p21, a cell‐cycle inhibitor and marker of cellular senescence, is upregulated in human liver disease and is a better prognostic marker than histological or clinical scoring systems. Objective: To quantify hepatocyte p21 immunopositivity in histopathology samples from dogs with CH and determine its association with outcome. Animals: Twenty‐six client‐owned dogs with histologically confirmed CH, and 15 dogs with normal liver histology. Methods: Medical records and liver histopathology samples were retrospectively reviewed to identify cases of CH. Immunohistochemistry for p21 was performed on all samples and hepatocyte immunopositivity was visually quantified. Relationships between p21 and dog age and dog survival time were statistically evaluated. Results: Hepatocyte p21 immunopositivity in dogs with CH was high (median percentage of positive hepatocytes: 90%, range: 20%‐98%) and exceeded 70% in 23/26 cases with no association with age. In control dogs, p21 immunopositivity was low (≤15% positive hepatocytes in 12/15 cases) and was positively correlated with age ( r s  = 0.63; P  = .011). Dogs with p21 immunopositivity exceeding 91.8% (upper tercile) had significantly shorter survival compared to dogs with less than 88.9% immunopositivity (lowest tercile; 218 versus 874 days, P  = .006). Increasing hepatocyte p21 immunopositivity was significantly negatively associated with survival time (HR 4.12; 95% CI 1.34‐12.63; P  = .013). Conclusions and Clinical Importance: Marked p21 immunopositivity in dogs with CH might be indicative of widespread hepatocellular senescence. A significant association with survival time also suggests a potential value for p21 quantification in determining prognosis.